B-type natriuretic peptide levels in patients with COPD and normal right ventricular function - İNANIR, SABAHAT; TOKAY TARHAN, SENA; ÖNEŞ, TUNÇ (SPRINGER, 2008)
Introduction: Evidence suggests that elevated plasma levels of B-type natriuretic peptide (BNP) are found in patients with chronic obstructive pulmonary disease (COPD) and right ventricular dysfunction. We examined the effects of exercise on plasma BNP levels in patients with COPD who have normal right ventricular function. Methods: Seventeen patients with a diagnosis of COPD and normal right ventricular function demonstrated by radionuclide ventriculography, and 17 age- and sex-matched healthy subjects underwent a treadmill exercise test. Plasma BNP levels were measured sequentially before, immediately after, and 1 hour after the exercise test. Results: The mean plasma BNP +/- standard deviation levels of the COPD and control groups before exercise were 21.3 +/- 16 pg/ml and 13.4 +/- 11 pg/ml, respectively (P>0.05). Mean plasma BNP level measured immediately after exercise was 37.9 +/- 31 pg/ml in the COPD group, reflecting a statistically significant increase when compared with the initial value (P<0.05). The control group did not show any significant change in plasma BNP levels after the exercise test. Conclusion: Exercise induces an increase in plasma BNP levels in patients with COPD who do not have right ventricular dysfunction at rest. Measurement of exercise-induced BNP levels may be a useful alternative to pulmonary artery catheterisation in identifying the patients who are likely to benefit from long-term oxygen therapy.
Keywords: brain natriuretic peptide; chronic obstructive pulmonary disease; right ventricle; OBSTRUCTIVE PULMONARY-DISEASE; TERM OXYGEN-THERAPY; BRAIN; HEMODYNAMICS; HYPERTENSION; DYSFUNCTION; BENEFITS; ATRIAL